Quasi alla fine della Storia del genere umano: la Proposta di premi fatta dall’Accademia dei Sillografi - Bellizzi, Aretina (Rivista Internazionale di Studi Leopardiani, 2024)
This essay examines the possibility that the “age of Machines” («età delle macchine»), as mentioned in the Proposta di premi fatta dall’Accademia dei Sillografi, might align with the concluding phase of the History of Mankind (Storia del genere umano) introduced in the Operette Morali. This phase would occur just before the ultimate end of mankind, which the Dialogo di un Folletto e di uno Gnomo suggests has already occurred. By delving into the reasons behind Leopardi’s decision to evoke the ancient “Sillographs”, and into their ties to other incomplete or endeveloped Disegni, this paper aims to differentiate Leopardi’s post-human perspective from conventional posthumanism. This differentiation commences with an exploration of the moral implications stemming from the interactions between human and machine, both present and prospective.